PENINGKATAN HASIL BELAJAR TEKNIK SHOOTING SEPAKBOLA SISWA SEKOLAH DASAR DENGAN PERMAINAN ‘ROLL BALL’ (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the improvement of learning outcomes shooting techniques soccer ball roll through the game in the fifth grade students of SDN 3 Gempolsewu district. Rowosari Kab. Kendal in 2013. The steps taken in this study begins with the ability to carry out pre-test students kicking and dribbling the ball and then compiled in accordance with the steps of problem identification is used, the data collection method used is a test technique and conducted an evaluation and reflection of the activities of planning, implementation, and the observation that collaborated with the Research Supervisor. The results of this study are based on the percentage of research data and results of pre-test and the conditions of the first cycle and second cycle, the implementation of learning results in the second cycle shows that the students do the shooting skills in playing football has increased. Data obtained with a descriptive analysis of the 2 percentages. the results of pre-test average value of the ability to dribble the ball and kicked it into the target by 71% to 76% in the first cycle of action execution, and increased again to 90% in the second cycle of learning implementation. The conclusion of the research refers to the ability of the technique of shooting in the fifth grade students of SDN 3 Gempolsewu, namely the implementation of learning soccer ball roll game model can improve motivation, response, activity and student learning outcomes.